Kerja terhadap Kinerja Karyawan di PT Pegadaian Syariah Cabang Metro Boulevard Cikarang - Dede Waqin; Dede Andriyana (Jurnal Al-fatih Global Mulia, 2022)
Performance is the result of employee work seen from the aspects of quality, quantity, working time, and cooperation to achieve the goals set by the organization or company. Employee performance will not produce maximum output or targets if it is not based on a high level of education and good experience. The higher the level of education, the higher the productivity and performance of the employee, as well as work experience, the more experienced the employee will occupy a higher position. The purpose of this study is to determine the effect of educational level on employee performance, to determine the effect of work experience on employee performance and to determine jointly the effect of education level and work experience on employee performance at PT Pegadaian Syariah Metro Boulevard Cikarang Branch. In this study the authors used the theory of educational level according to (Nurkholis, 2013) and work experience according to (Hermawan, 2017) and the theory of employee performance according to (Hendrayani, 2020). The method used in this study is a quantitative method by distributing questionnaires. Subjects in this study used a sample of 32 respondents. The sampling technique uses the census method or total sampling. Sources of data used in this study are primary data and secondary data. The data analysis method used in this study is the classical assumption test, hypothesis test, correlation test, multiple linear regression test and test the coefficient of determination using SPSS version 25 for windows. The results of the study showed that the variable level of education had an effect on employee performance at PT Pegadaian Syariah Metro Boulevard Cikarang Branch, this can be seen from the results of the t test on the education level variable showing that the t_count value is 2.977 > t_table is 2.042. Work experience also turns out to have an effect on employee performance at PT Pegadaian Syariah Metro Boulevard Cikarang Branch, this can be seen from the results of the t test on the work experience variable showing that the t_count value is 2.142 > from t_table is 2.042. The results of the F test show that the F_count value is 25.919 F_count > F_table (25.919 > 3.32), so it can be said that the variable Level of Education (X1) and Work Experience (X2) simultaneously or jointly affect Employee Performance (Y)